2005
DOI: 10.1007/s00280-005-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytokinesis and akt phosphorylation by chaetoglobosin K in ras-transformed epithelial cells

Abstract: Our results demonstrate that ChK inhibits Akt kinase phosphorylation and cytokinesis in ras-transformed cells, which likely contribute to its ability to inhibit tumorigenic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 33 publications
4
16
0
1
Order By: Relevance
“…We previously reported that ChK down-regulates the Akt pathway in ras-transformed epithelial cells (5). In those studies, 2-10 mM ChK induced decreased Akt phosphorylation at 4-72 h treatment times.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We previously reported that ChK down-regulates the Akt pathway in ras-transformed epithelial cells (5). In those studies, 2-10 mM ChK induced decreased Akt phosphorylation at 4-72 h treatment times.…”
Section: Discussionmentioning
confidence: 98%
“…Chaetoglobosin K (ChK) is a natural product compound isolated from Diplodia macrospora (3) that has previously been shown to suppress the tumorigenic phenotype in transformed fibroblasts (4), and inhibit growth of ras-transformed liver epithelial cells (5). It has also been shown to prevent inhibitory effects of tumor promoting organochlorine compounds on gap junction-mediated cell-cell communication in astroglial and epithelial cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…This method was slightly modified from a previously published method [9]. Briefly, cells grown in 35 mm dishes were washed once with PBS containing 0.5 mM CaCl 2 , 0.5 mM MgCl 2 (Ca 2+/ Mg 2+ PBS, to prevent cell detachment) and twice in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Cell proteins were extracted using a 2% SDS total protein extraction method [9]. Protein in each sample was quantified using the Bio-Rad DC protein assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation